Challenges of Kenya’s Vision 2030 and the Jubilee Manifesto: the Case of Old People Cash Transfer Pension Scheme in Nakuru County - Kindiki, Moses Mpuria; Wambu, Charles (Redfame Publishing, 2015)
Most Kenyans lack financial resources for retirement and rely on their families, yet the family is becoming a less reliable source of support in old age due to decreasing fertility and the increasing mobility of the young. In response, and as one of the strategies of realising Vision 2030, the Kenyan government has established an Old People Cash Transfer Pension Scheme (OPCTPS) as a form of social protection for the elderly. This study focused on the challenges of the OPCTPS in Kenya under the Jubilee Coalition government that came to power in 2013. The study used survey research design and the target population was sampled randomly from a list of registered beneficiaries to form 340 respondents and 10 key informants. The data was collected using questionnaires for key informants and interview schedules for the respondents. The data was analysed using Statistical Package for Social Science computer program and was presented using descriptive statistics. The results of the study showed that the challenges which hindered implementation of the OPCTPS, in order of importance, include low coverage, low allocation of funds, credibility in management, delays in payments, high administrative costs, poor awareness and lack of relevant documents. The study findings may be used by policy makers to plan for better coverage of the OPCTPS. Also the results may be used by stakeholders to strategies on how to empower the aged and ageing people and in allocation of domestic resources. Above all, the Jubilee Coalition government in power should spearhead the passing of at least one Act of Parliament to consolidate the existing legal framework and policy on the OPCTPS.
Keywords: Old age; Cash transfer; Pension; Beneficiary; Stakeholder